The Impact of COVID-19 on Hospital Admissions in Croatia - Kalanj, Karolina; Marshall, Ric; Karol, Karl; Tiljak, Mirjana Kujundžić; Orešković, Stjepan (Frontiers in Public Health, 2021)
Background: The Covid-19 pandemic disrupted hospital care, as hospitals had to deal with an infectious virus, while at the same time trying to fulfill the ongoing health service needs of their communities. The study examines the direct effects of Covid-19 on the delivery of inpatient care in Croatia. Materials and Methods: The research is a comparative analysis of the hospital admission rate across all DRG classes before and during the Covid-19 pandemic. It used DRG data from all non-specialized acute hospitals in Croatia, which account for 96% of the national in patient activity. It also uses data from the Croatian Public Health Institute’s (PHI) Covid-19 database. Results: It was found that in 2020, there was a 21% decrease in the total number of admissions across the hospital network, with the greatest drop occurring in April 2020, when admissions plunged by 50%. The decrease in activity occurred in cancers (14%), as well as in non-elective DRG classes such as: Stroke; Major Chest Procedures; Heart Failure & Shock; and Renal Failure. Coinciding with this reduction however, there was a 37% increase in case activity across six Covid-19 related DRG classes. Conclusions: The reduction in hospital inpatient activity during the Covid-19 period in Croatia, was due to a mix of factors such as lock-down and associated quarantining, reorganizations of hospital operations, and medical workforce rationing. Further research is needed to examine the aftermath of the disruption to hospital care in Croatia. Also, a review of response procedures to emergencies such as Covid-19 should be undertaken with the aim of minimizing their adverse effect on other, and equally important community health care needs.